The phytochemical components of Kelantan grown Annona muricata leaves and its anti-proliferative properties on MCF-7 breast cancer cells - Norzila Ismail; Harishini Rajaratinam; Khairunnisa Che Ghazali; Siti Farhanah Mohd Salleh; Wan Suriyani Faliq Adeeba Wan Ibrahim; Maya Mazuwin Yahya; Wan Zainira Wan Zain (Penerbit Universiti Kebangsaan Malaysia, 2023)
Annona muricata leaves exhibit anti-cancer properties against breast cancer. In this study, the phytochemical components, anti-proliferative activity, and cytotoxicity of Kelantan (Malaysia) grown Annona muricata leaves were evaluated using MCF-7 breast cancer cell line. The preparation of Annona muricata leaves extracts was performed with various organic solvents (ethyl acetate, n-hexane, methanol, and aqueous) using Soxhlet method. Each extract was analysed using gas chromatography-mass spectrometry (GCMS) for phytochemical analysis and characterised with Wiley and NIST library searchers. The effects of all extracts on cell proliferation were analysed using MTT assay. The anti-proliferative activity was determined by evaluating the IC50 value. Based on the lowest IC50 value, further experiments were done to observe the apoptosis effect using the Annexin V-FITC technique. While for cell cycle analysis, Cycletest Plus DNA Reagent Kit was used. Both were further determined using flow cytometry analysis. The ethyl acetate-based Annona muricata extract contained terpenoids, phenolic compounds, and alkaloids. Ethyl acetate extract of Annona muricata exhibited a significant cytotoxic effect on MCF-7 breast cancer cells. The most potent IC50 value obtained was 21.8 ± 3.85 µg/mL. The changes in morphology were more profound after 72 h of treatment with ethyl acetate extract of Annona muricata, including cell shrinkage. Flow cytometry analysis showed that it was induced in early and late apoptosis in vitro and arrest at G0 /G1 cell cycle phase in time-dependant manners. In short, ethyl acetate extract of Annona muricata exhibited a range of phytochemical components, anti-proliferative activity and cytotoxic effect on MCF-7 breast cancer cells.